X-LAB: A very high-capacity X-band RF test stand facility at the University of Melbourne - Volpi Matteo; Giansiracusa Paul J.; Sheehy Suzanne L.; Rassoll Roger P.; Taylor Geoffrey N.; Pushkarna Paarangat; Dowd Rohan; Valerian Joel; Catalan-Lasheras Nuria; Cherrill Mark (EPJ Web of Conferences)
The X-band Laboratory for Accelerators and Beams (X-LAB) has been commissioned at the University of Melbourne. One of the key projects within this laboratory involves re-homing half of the CERN high gradient X-band test stand, XBOX3, now known as Mel-BOX. This initiative aims to validate the performance of high-gradient travelling wave accelerating structures operating at a frequency of 12 GHz, which are a crucial component of the acceleration baseline for the Compact Linear Collider (CLIC). Mel-BOX will be employed to assess the performance of these accelerating structures under high power pulsed RF. As with XBOX3, Mel-BOX uses the combined power from two high average power klystron units to feed two test slots at a repetition rate of up to 400 Hz. Additionally, the parameters such as repetition rate, peak power, pulse length, and pulse shape can be tailored to meet specific test requirements. This method of generating high-power, high-repetition RF pulses holds promise for various applications necessitating multiple test slots. Moreover, there are plans to leverage this technology as a foundation for developing compact accelerators tailored for medical or university applications, including radiotherapy and compact light sources.